On the Distribution of the Mean and Variance of a Quantitative Trait under Mutation-Selection-Drift Balance - Burger, R. (1994)
The distributions of the mean phenotype and of the genetic variance of a polygenic trait under a balance between mutation, stabilizing selection and genetic drift are investigated. This is done by stochastic simulations in which each individual and each gene are represented. The results are compared with theoretical predictions. Some aspects of the existing theories for the evolution of quantitative traits are discussed. The maintenance of genetic variance and the average dynamics of phenotypic evolution in finite populations (with N(e) < 1000) are generally simpler than those suggested by some recent deterministic theories for infinite populations.